Measuring the performance of knowledge resources using a value perspective: integrating BSC and ANP. Issue 6 (12th October 2015) - Hu, Yaoguang; Wen, Jingqian; Yan, Yan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide insight into how knowledge resources in R & D organizations can be effectively and separately measured for knowledge sharing and transfer. Knowledge is recognized as a durable strategic resource to obtain sustainable competitive advantage. Design/methodology/approach – The paper proposes a theoretical framework integrating an analytic network process (ANP) with a balanced scorecard (BSC) to measure the performance of knowledge resources under value perspective. Four indicators and three knowledge value (KV) components including labor value, technology value and utilization value are discussed. The model construction, problem structuring and calculation procedure for measuring the performance of knowledge resources based on ANP and BSC are demonstrated. Findings – Despite a number of models to assess the performance of knowledge resources being proposed, they highlighted a need for separately measuring under value perspective. With the aim of filling this gap, the main finding of the paper is to clarify relevant issues, providing a better framework for assessment of the performance of knowledge resources. Research limitations/implications – To handle the dynamic nature of knowledge, the research should take into account more advanced methods to measure the performance of knowledge resources. Both qualitative and quantitative methods should be utilized in future research. Practical implications – The consequences of measuring the performance of knowledge resources under value perspective may help managers to organize and arrange the separate knowledge resources, improving the knowledge resources exchange between different institutions in R & D organizations. Originality/value – The main contribution of this paper lies in the development of a comprehensive model, which incorporates diversified issues for conducting the performance of knowledge resources under value perspective.